Elevated Tissue Factor and Tissue Factor Pathway Inhibitor Circulating Levels in Ischaemic Heart Disease Patients - Falciani, Michela; Gori, Anna Maria; Fedi, Sandra; Chiarugi, Ludia; Simonetti, Ignazio; Dabizzi, Roberto Piero; Prisco, Domenico; Pepe, Guglielmina; Abbate, Rosanna; Gensini, Gian Franco; Serneri, Gian Gastone Neri (Thrombosis and Haemostasis, 1998)
Several studies have shown that thrombosis and inflammation play an important role in the pathogenesis of Ischaemic Heart Disease (IHD). In particular, Tissue Factor (TF) is responsible for the thrombogenicity of the atherosclerotic plaque and plays a key role in triggering thrombin generation. The aim of this study was to evaluate the TF/Tissue Factor Pathway Inhibitor (TFPI) system in patients with IHD.We have studied 55 patients with IHD and not on heparin [18 with unstable angina (UA), 24 with effort angina (EA) and 13 with previous myocardial infarction (MI)] and 48 sex- and age-matched healthy volunteers, by measuring plasma levels of TF, TFPI, Prothrombin Fragment 1-2 (F1+2), and Thrombin Antithrombin Complexes (TAT).TF plasma levels in IHD patients (median 215.4 pg/ml; range 72.6 to 834.3 pg/ml) were significantly (p<0.001) higher than those found in control subjects (median 142.5 pg/ml; range 28.0-255.3 pg/ml).Similarly, TFPI plasma levels in IHD patients were significantly higher (median 129.0 ng/ml; range 30.3-316.8 ng/ml; p <0.001) than those found in control subjects (median 60.4 ng/ml; range 20.8-151.3 ng/ml). UA patients showed higher amounts of TF and TFPI plasma levels (TF median 255.6 pg/ml; range 148.8-834.3 pg/ml; TFPI median 137.7 ng/ml; range 38.3-316.8 ng/ml) than patients with EA (TF median 182.0 pg/ml; range 72.6-380.0 pg/ml; TFPI median 115.2 ng/ml; range 47.0-196.8 ng/ml) and MI (TF median 213.9 pg/ml; range 125.0 to 341.9 pg/ml; TFPI median 130.5 ng/ml; range 94.0-207.8 ng/ml). Similar levels of TF and TFPI were found in patients with mono- or bivasal coronary lesions. A positive correlation was observed between TF and TFPI plasma levels (r = 0.57, p <0.001). Excess thrombin formation in patients with IHD was documented by TAT (median 5.2 μg/l; range 1.7-21.0 μg/l) and F1+2 levels (median 1.4 nmol/l; range 0.6 to 6.2 nmol/l) both significantly higher (p <0.001) than those found in control subjects (TAT median 2.3 μg/l; range 1.4-4.2 μg/l; F1+2 median 0.7 nmol/l; range 0.3-1.3 nmol/l).As in other conditions associated with cell-mediated clotting activation (cancer and DIC), also in IHD high levels of circulating TF are present. Endothelial cells and monocytes are the possible common source of TF and TFPI. The blood clotting activation observed in these patients may be related to elevated TF circulating levels not sufficiently inhibited by the elevated TFPI plasma levels present.